verify the following (c) (-9) [(-4) + 11] = (-9) * (-4) + (-9) x 11
Answers
Answered by
0
Answer:
please write the answer
Attachments:
![](https://hi-static.z-dn.net/files/d6c/9616eb05a93f9cad7f38232adba16736.jpg)
Answered by
1
Answer:
(c) (-9) [(-4) + 11] = (-9) * (-4) + (-9) x 11
(-9)(7) = 36-99
-63 = -63
L.H.S = R.H.S
hope it will help you dear ☺️
Similar questions
Math,
1 month ago
Chemistry,
1 month ago
Physics,
1 month ago
Math,
3 months ago
Social Sciences,
3 months ago
Social Sciences,
11 months ago
English,
11 months ago